NEW APPROACHES TO ORGANIZING RARE BOOKS EXHIBITIONS IN MUSEUMS AROUND THE WORLD - Azimova, Ganjina (Journal of Learning on History and Social Sciences, 2024)
General Background: Museums play a crucial role in preserving cultural heritage and enhancing public engagement with historical artifacts. Specific Background: Recent advancements in exhibition design and curation have transformed traditional museum practices, enabling more interactive and immersive experiences for visitors. Knowledge Gap: Despite the growing body of literature on innovative exhibition methods, there is a lack of comprehensive analysis regarding their effectiveness and the integration of rare books into these contemporary practices. Aims: This study aims to evaluate new approaches to exhibition organization in museums worldwide, focusing specifically on the incorporation of rare books as a central element of these exhibitions. Results: Our findings indicate that museums implementing interactive and thematic frameworks not only improve visitor engagement but also enhance the educational value of rare books displayed. Case studies from various institutions reveal diverse strategies that effectively highlight the significance of these artifacts. Novelty: This research contributes to the discourse on museum studies by providing a systematic overview of innovative exhibition methodologies, particularly emphasizing the role of rare books in enhancing cultural narratives. Implications: The insights gleaned from this study can inform museum curators and educators about best practices in exhibition design, potentially leading to increased visitor interest and greater appreciation of rare literary works. By bridging the gap between traditional and modern curation techniques, museums can foster deeper connections with their audiences, ultimately enriching the cultural landscape.